Influence of the storage duration to survival, toxicity and reproduction of some entomopathogenic nematode strains genera Steinernema and Heterorhabditis - My, Vu Tu; Chau, Nguyen Ngoc (Academia Journal of Biology, 2014)
The influence of storage duration of infective juveniles (IJs) of entomopathogenic nematodes, viz. S-TX1, S-XS4 (Steinernema sangi) and H-NT3 and H-MF11 (Heterorhabditis indica) to themselves survival ratio (LT), toxicity (LC50) and reproduction capacity in Galleria mellonella (IJJs/GM) were assessed in the Laboratory condition. The assays results showed three these above indexes reduced in duration of storage, though they were different between Steinernema and Heterorhabditis strains. In strains of Steinernema the survival 50% ratio  (LT50) was stable after 12 months in storage whereas LC50 and reproduction capacity were stable after 8-9 month in storage and Steinernema strains can be survived up to 20 month-storage but their toxicology and reproduction capacity were exhausted at 12-13 months in storage. In strains of Heterorhabditis, these indexes occurred in earlier. The survival ratio 50% (LT50), LC50 and reproduction capacity were stable after 6 months in storage. Heterorhabditis strains can be survived up to 12 months in storage condition but their toxicity and reproduction capacity were exhausted at 10-month storage. The storage duration of IJs was related closely with the lipid amount reserved in IJs intestine. Due to the large body size in Steinernema juveniles and the biger amoun of lipid reseved in their intestine they are significantly longer survival than Heterorhabditis juveniles. The decreasing the lipid in during storage was observed and its to be exhausted at timing that infective juvenile to be died.